АСПЕКТУАЛ ФРЕЙМНИНГ НАЗАРИЙ АСОСЛАРИ - Мирсанов, Ғ. (SCIENCE and SOCIETY, 2017)
The article deals with the study of aspectual semantics in frame field and there are suggestions on the theoretical basis of this approach. The language units in actual frames have complex structural and semantic forms. The differences of language units and predicates from the semantic point of view, are connected with concordance and information. The main content of the article is to differentiate theoretical approaches to frame and field.